BHD-associated kidney cancer exhibits unique molecular characteristics and a wide variety of variants in chromatin remodeling genes. (14th May 2018) - Hasumi, Hisashi; Furuya, Mitsuko; Tatsuno, Kenji; Yamamoto, Shogo; Baba, Masaya; Hasumi, Yukiko; Isono, Yasuhiro; Suzuki, Kae; Jikuya, Ryosuke; Otake, Shinji; Muraoka, Kentaro; Osaka, Kimito; et al.
Abstract: Birt–Hogg–Dubé (BHD) syndrome is a hereditary kidney cancer syndrome, which predisposes patients to develop kidney cancer, cutaneous fibrofolliculomas and pulmonary cysts. The responsible gene FLCN is a tumor suppressor for kidney cancer, which plays an important role in energy homeostasis through the regulation of mitochondrial oxidative metabolism. However, the process by which FLCN -deficiency leads to renal tumorigenesis is unclear. In order to clarify molecular pathogenesis of BHD-associated kidney cancer, we conducted whole-exome sequencing analysis using next-generation sequencing technology as well as metabolite analysis using liquid chromatography–mass spectrometry and gas chromatography–mass spectrometry. Whole-exome sequencing analysis of BHD-associated kidney cancer revealed that copy number variations of BHD-associated kidney cancer are considerably different from those already reported in sporadic cases. In somatic variant analysis, very few variants were commonly observed in BHD-associated kidney cancer; however, variants in chromatin remodeling genes were frequently observed in BHD-associated kidney cancer (17/29 tumors, 59%). Metabolite analysis of BHD-associated kidney cancer revealed metabolic reprogramming toward upregulated redox regulation which may neutralize reactive oxygen species potentially produced from mitochondria with increased respiratory capacity under FLCN -deficiency. BHD-associated kidney cancer displays unique molecular characteristics that are completely different from sporadic kidney cancer, providing mechanistic insight into tumorigenesis under FLCN -deficiency as well as a foundation for development of novel therapeutics for kidney cancer.